‘n Christosentriese koinonia-dinamiek agter Paulus se hantering van sekere problematiek in 1 Korintiërs - De Wet, B. W. (Verbum et ecclesia, 2006)
This article reasons that Paul tends to use a Christosentric koinonia-dynamic as a paradigm for addressing some of the problems in 1 Corinthians. As a test case the problem of the eating of food (especially meat), consecrated and/or sacrificed to the idols during social, as well as cultic occasions, as formulated in 8:1a was chosen. Being part of the macro structure of 8:1-11:1 it becomes clear, especially from 10:14-22 that Paul uses especially the dynamic of a Christosentric koinonia paradigm to address this problem. Focusing on the intensity of koinonia, as it functioned within the holy communion and the sacrificial meal of the Israelites, Paul motivates the Corinthians not to have anything to do with sacrificial heathen meals.